Ethnoscience Course Program Oriented Towards Education for Sustainable Development (ESD): A Needs Assesment - Ilhami, Aldeva; Hidayat, Topik; Riandi, Riandi; Sriyati, Siti (SEARCH: Science Education Research Journal, 2026)
Ethnoscience is one of the compulsory courses in the Science Education program. The implementation of Education for Sustainable Development (ESD) should be integrated into the ethnoscience course to enhance the awareness of prospective science teachers regarding the environment and sustainability. This study aims to analyze the implementation of the ethnoscience course program at a Teacher Training Institution (LPTK) in Riau Province. A case study methodology was employed, involving the analysis of ethnoscience course documents, observation and interviews with lecturers. The data were analyzed using qualitative descriptive methods based on the Miles-Huberman framework. The course implementation plan has met the established standards, and the majority of the learning outcomes align with the qualifications set by the Indonesian National Qualification Framework (KKNI). The ethnoscience course uses a research approach that examines the reconstruction of indigenous knowledge into scientific knowledge, though it has yet to emphasize sustainability literacy. Lecturers face challenges in accommodating the depth of content derived from student projects. Stakeholders should consider policies for collaborative teaching,like citizen science project in ethnoscience to support the optimization of achieving the course’s expected competencies.